A Study on Financial Health of Textile Industry in India: A 'Z'-Score Approach - Raiyani, J. R.; Bhatasna, R. B. (Indian Journal of Finance, 2011)
Although an individual ratio may indicate a particular strength or weakness in a company, no individual ratio can adequately evaluate the overall strength or weakness in a company. Developed by Edward I. Altman in 1968, the Altman Z-Score has become one of the most accepted and tested predictors of bankruptcy potential for a firm. Although it was originally developed from a sample of manufacturing firms, it is also applied to nonmanufacturing firms. Essentially, it considers strength or weakness in five key ratios as an indication of a firm's bankruptcy potential. The study attempts to assess the financial Health of the sample companies in terms of retained earning to total assets position, networking capital position, Equity-debt position. Return on total assets position and Net sales turnover position of the sample companies. The study on Financial Health of Textile Industry in India has been made by using data from financial statements of all four major players in Textile industry- they are Siyaram Silk Mills Ltd.(SSML), Shri Dinesh Mills Ltd.(SDML), Welspun India ltd.(WIL), S. Kumars Nationwide Ltd.(SKNL). The period of the study was of seven years from 2002-03 to 2008-09. For the purpose of analysis, the researcher has used Altman's 'Z' score to predict, analyze and compare the financial health of the sample companies and different ratios are calculated, the simple statistical techniques such as mean and ANOVA test were also applied to analyze the consistency, stability and overall trends in the different ratios used in Altman's 'Z' score approach.